Effect of ceftiofur and enrofloxacin on E. coli sub-population in pig gastrointestinal tract. (September 2017) - Lin, Dachuan; Chen, Kaichao; Xie, Miaomiao; Ye, Lianwei; Chan, Edward Wai-Chi; Chen, Sheng
Highlights: The study investigated the effects on antibiotic treatment on antibiotic resistant sub-population organisms in animal GI tract. Antibiotic resistant organisms constituted a varied but significant proportion of the gut flora regardless of the degree of previous exposure to antibiotics. The proportion of sub-population of resistant organisms varied according to the presence of antibiotic pressure. Increase of ceftiofur-resistant subpopulation was mainly attributed to transmission of blaCTX-M -borne plasmids. Abstract: Background: Antibiotic resistant sub-population of the gut microbiome in both human and animals may be enriched during antimicrobial treatment. Methods: This study investigated how the size and antibiotic susceptibility profiles of antibiotic resistant sub-population organisms in the animal gastrointestinal tract changed upon exposure to different levels of ceftiofur and enrofloxacin by plating fecal samples collected from piglets before and after antibiotic treatment onto MacConkey agar containing 0.5 μg/ml cefotaxime and determination of the resistance rate. Genetic characteristics and relatedness of strains collected before and after treatment was tested to determine if resistant Escherichia coli strains that emerged after treatment was due to dissemination of resistance-encoding mobile elements or clonal expansion of specific strains. Results: Antibiotic resistant organisms constituted a varied but significant proportion of the gut flora regardless of the degree of previous exposure to antibiotics; the proportion of sub-population resistant organisms in the gut flora decreased but remained detectable even 10 days after antibiotic selection pressure had been relieved, and increased again upon renewed exposure to antibiotic regardless of the approach of administration. The increased prevalence of cefotaxime resistant strains in the animal GI tract upon treatment with sub-therapeutic and therapeutic concentrations of ceftiofur/enrofloxacin was respectively attributed to transmission of blaCTX-M -borne plasmids and clonal expansion of pre-existing resistant strains. Conclusion: The gut flora of animals comprises a high baseline level of resistance, among which resistant organisms cannot be eradicated but instead being further enriched in successive episodes of antibiotic treatment.